The benefits and challenges of mobile banking at the Bottom of the pyramid - Purohit, Dr. Sonal; Arora, Dr. Rakhi (The journal of contemporary issues in business and government, 2021)
Financial inclusion envisages bringing the people into the formal banking sector and mobile banking can help in this task. It is estimated that almost 85% of the BoP population in the world uses mobile phones but, whether the mobile banking will actually help the BoP and fulfill the purpose of financial inclusion remains a question. Limited research has been conducted on mobile banking among the BoP and has mainly focused on the mobile banking adoption and its determinants. The benefits and challenges of mobile banking to the poor have not been discussed in the past. Before working on the potential solutions of mobile banking, a serious thought over if the mobile banking will actually help the poor or in what ways can help in preparing a strategy that can integrate the positioning of the benefits of mobile banking solutions. Thus, through this research we aim to discuss the benefits and challenges of mobile banking to the BoP. The benefits of mobile banking to the BoP are reduced cost, reduced time and personalization. The challenges of mobile banking are related to system, security, regulatory environment, economic viability. The service providers should work closely with the government agencies to develop appropriate systems that can overcome the challenges and increase the benefits in order to encourage the use of mobile banking at the BoP.